The Privacy Paradox in Smart Classrooms: Balancing Data-Driven Personalization with Student Data Protection and Ethical Governance - Rit Som; Pierre Ndayizeye; Alida Ntahonkiriye (Yayasan Adra Karima Hubbi, 2026)
Background: The integration of smart technologies in classrooms has significantly enhanced personalized learning by utilizing data analytics to cater to individual student needs. However, the increasing reliance on student data has raised concerns about privacy, security, and ethical governance, creating what is known as the